PRACTICAL ASPECTS OF DEVELOPMENT OF CULTURE IN THE DIGITAL ECONOMY - Safarov Laziz Sayimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The influence of digital technologies in the modern world, deep in all spheres of life shows. The internet, mobile devices, social networks and other digital platforms plays a central role in the formation of human activity and cultural life. Digital life — not only this process, but the communication between people, creativity and is regarded as a new form of sharing knowledge.